(untitled) (Journal of Economic Research & Business Administration, 2015)
The research questions of budgetary and fiscal equalization regionalism it assumes forming a model that allows , on the one hand, the integrity of the state in a single policy , and on the other - an acceptable level of autonomy of local budgets. This paper considers the current state of the mechanism of intergovernmental transfers in the Republic of Kazakhstan. Conducted correlation between allocated transfers and fiscal instrument. This article aims to identify the main problems and challenges facing local authorities , which should be implemented in the context of limited financial resources